Implementasi Gerakan ABABIL: Membangun Budaya Literasi di MI Ihyauddiniyah Probolinggo - Azharghany, Rojabi; Titik Bawon; Eva Suryana (Yayasan Literasi Altruis Khatulistiwa, 2025)
This community service activity carries the theme of the Implementation of the Ayo Bangkit Bina Literacy (ABABIL) Movement which was carried out at MI Ihyauddiniyah, Sareh Hamlet, Duren Village, Probolinggo Regency. This school has great potential in developing a culture of literacy, supported by the involvement of cooperative teachers and available free space. However, several challenges are still faced, such as low student interest in reading, limited facilities and extracurricular literacy programs, and the lack of a consistent reading culture. The low interest in reading was identified through observations of student habits regarding access to reading materials, the level of activity in reading sessions, and the results of a diagnostic questionnaire that measures reading frequency, reading duration, and interest in various types of reading. This program aims to build a sustainable literacy ecosystem through optimizing the reading space and the active involvement of all school members. The program implementation method is designed in five stages: (1) needs analysis using a participatory SWOT approach, (2) collaborative activity planning between students, teachers, and pupils, (3) literacy training through story writing classes, critical reading, public speaking, and small da'wah, (4) implementation of literacy activities in the form of daily practice in the reading room and school forum, and (5) monitoring and evaluation to measure the effectiveness of the program and develop follow-up actions. The results of the activities show the formation of an active reading room that is used routinely, increased student participation in literacy activities, and the growth of students' self-confidence and communication skills. This program is a collaborative model between students, teachers, and pupils in building a contextual and sustainable literacy culture in the elementary education environment.